Problems and Solutions in Thermoelasticity and Magneto-thermoelasticity - Das, B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents problems and solutions of the mathematical theories of thermoelasticity and magnetothermoelasticity. The classical, coupled and generalized theories are solved using the eigenvalue methodology. Different methods of numerical inversion of the Laplace transform are presented and their direct applications are illustrated. The book is very useful to those interested in continuum mechanics.
Basic Ideas -- Vector-matrix Differential Equation -- Coupled Thermoelasticity -- Generalized Thermoelasticity -- Generalized Magnetothermoelasticity.
Keywords: Mechanics, Applied; Solids; Physics; Mathematics; Solid Mechanics; Classical and Continuum Physics; Applications of Mathematics